2018
DOI: 10.1021/jacs.8b01601
|View full text |Cite
|
Sign up to set email alerts
|

Electron Injection from Photoexcited Metal–Organic Framework Ligands to Ru2 Secondary Building Units for Visible-Light-Driven Hydrogen Evolution

Abstract: We report the design of two new metal-organic frameworks (MOFs), Ru-TBP and Ru-TBP-Zn, based on Ru secondary building units (SBUs) and porphyrin-derived tetracarboxylate ligands. The proximity of Ru SBUs to porphyrin ligands (∼1.1 nm) facilitates multielectron transfer from excited porphyrins to Ru SBUs to enable efficient visible-light-driven hydrogen evolution reaction (HER) in neutral water. Photophysical and electrochemical studies revealed oxidative quenching of excited porphyrin by Ru SBUs as the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 29 publications
7
107
0
Order By: Relevance
“…W-TBP and Bi-TBP nMOFs were synthesized through solvothermal reactions between 5,10,15,20-tetra(p-benzoato)porphyrin (H 4 TBP) and WCl 6 or Bi(NO 3 ) 3 ·5 H 2 Oi nN ,Ndimethylformamide and acetic acid at 80 8 8C. TEM imaging revealed similar rectangular nanoplate-like morphologies (Figure 1a PXRD studies revealed that W-TBP is isostructural to previously reported Ru-TBP (Figure 2a;S upporting Information, Figure S3), [14] while Bi-TBP has the same structure as its bulk phase whose structure was determined by singlecrystal X-ray diffraction (Supporting Information, Table S1). In W-TBP,TBP ligands are linked by dinuclear W-oxo SBUs to form ac ationic 3D framework with af ormula of [W 2 -(TBP)(H 2 O) 2 ] 8+ .I nB i-TBP,T BP ligands are linked by infinite Bi-oxo chains to afford an eutral 3D framework with af ormula of Bi 2 (TBP)(O) (Supporting Information, Figures S1, S2).…”
supporting
confidence: 65%
“…W-TBP and Bi-TBP nMOFs were synthesized through solvothermal reactions between 5,10,15,20-tetra(p-benzoato)porphyrin (H 4 TBP) and WCl 6 or Bi(NO 3 ) 3 ·5 H 2 Oi nN ,Ndimethylformamide and acetic acid at 80 8 8C. TEM imaging revealed similar rectangular nanoplate-like morphologies (Figure 1a PXRD studies revealed that W-TBP is isostructural to previously reported Ru-TBP (Figure 2a;S upporting Information, Figure S3), [14] while Bi-TBP has the same structure as its bulk phase whose structure was determined by singlecrystal X-ray diffraction (Supporting Information, Table S1). In W-TBP,TBP ligands are linked by dinuclear W-oxo SBUs to form ac ationic 3D framework with af ormula of [W 2 -(TBP)(H 2 O) 2 ] 8+ .I nB i-TBP,T BP ligands are linked by infinite Bi-oxo chains to afford an eutral 3D framework with af ormula of Bi 2 (TBP)(O) (Supporting Information, Figures S1, S2).…”
supporting
confidence: 65%
“…Different from traditional photocatalysts, MOFs show some distinct photocatalytic properties arising from metal node, organic linker or both . To effectively separate electron and hole generated by light irradiation and improve the catalytic efficiency, MOFs are promising hosts for encapsulating electron acceptors and semiconductive NPs, such as metals, metal oxides, POMs, photoactive metal complexes or dyes, in which they will generate intriguing synergy functions compared with single counterparts.…”
Section: Catalytic Performances Of Active Nps Encapsulated By Mofsmentioning
confidence: 99%
“…As a result, their Zr porphyrinic MOF‐545/CoPOM hybrid can facilitate efficient charge transfer between porphyrin and CoPOM molecules and thus be used as an oxygen‐evolving photocatalyst in the form of a powder dispersion. Lan et al reported the incorporation of both organometallic photosensitizers and HER electrocatalysts using Ru(4‐ tert ‐butylpyridine) and porphyrinic ligands as a building block of the MOFs for photocatalytic hydrogen production by means of powder dispersion . It is also possible to utilize building block ligands with multiple metal‐binding groups – main groups for the formation of MOFs and additional ones for the attachment of organometallic compounds.…”
Section: Immobilization Of Molecular Electrocatalysts Via Physicalmentioning
confidence: 99%